CCHSA accreditation An instigator for change and a motivator for health human resources: A case study of a health region in Alberta - Tosh, Amy Elizabeth (University of Ottawa (Canada), 2006)
There are many unanswered questions regarding the influence and effectiveness of accreditation programs on healthcare services. Many participants advocate the value of the process and site reform and success experienced as a result of sharing in a program. However, there are many health service providers who have not chosen to participate. This single case study has been initiated as an opportunity to investigate the impact of an accreditation program on a health region and examine the consequences and results of the process on that organization. This study specifically focuses on the impact the process has on teams within the health organization. This report will be used in a broader multi-case study comparison to view similarities and differences in the results of accreditation. The site of this specific case study was an Alberta Health Region. The accreditation process was undertaken in this region for the first time in the history of the organization under the regional model. (Abstract shortened by UMI.)
Keywords: Business Administration, Management.; Health Sciences, Health Care Management.